Jayne Mansfield's car [videorecording (DVD)] - Thornton, Billy Bob; Thornton, Billy Bob; Thornton, Billy Bob; Duvall, Robert; Hurt, John, 1940-2017; Bacon, Kevin, 1958- (Anchor Bay Entertainment, 2013)
Two families from different countries come together and try to coexist in a small Alabama town in 1969.